Pengetahuan Pengetahuan Merupakan Bentuk Cinta Menurut Erich Fromm dalam Film Amour Karya Michael Haneke - Azzahra, Yosfia; Dewi, Evi Rosyani; Ismail, Subur (Franconesia, 2024)
This research aims to describe the role or function of knowledge as a form of love criteria according to Erich Fromm. This research uses the main theory of Elements of Love which comes from the book The Art of Loving: 4th Edition by Erich Fromm (2021). There are four (4) types of love elements included in the Elements of Love theory, namely Care, Responsibility, Respect and Knowledge. This research uses a content analysis method which consists of six (6) stages, namely (1) Forming and formulating questions, (2) Determining the theoretical background of the research, (3) Data collection, (4) Selecting and determining research methods, (5) ) Data analysis, and (6) Reflecting on research implications and discussions. The analysis technique in this research uses an interactive data analysis model from Miles and Huberman with three (3) stages, namely 1) Data reduction stage 2) Data presentation stage and 3) Conclusion drawing or data verification stage. The research results show 34 (thirty four) quotes that show the form of interpretation of love in the film Amour by Michael Haneke. The element of love that dominates in the film is attention with 12 (twelve) elements in the form of care and sincerity. Then, the second form is responsibility with 14 (fourteen) quotes, respect with 3 (three) quotes and finally knowledge with 5 (five) quotes.